Cosmetic Surgery or Amputation? A Necessary Debate from the Perspective of Animal Welfare and Health - Gutiérrez-Velez, Edgar; Acero-Plazas, Víctor Manuel; Maluk-Duque, Fernando; Beltrán-Ríos, Karol Bibiana; Roa-Castellanos, Ricardo Andrés (Spei Domus, 2019)
Purpose: To present a historical, medical and regulatory approach, within the Colombian context, around the assessment of certain surgical procedures regarded as aesthetic. The aim is to promote reflection on their suitability and applicability from science, considering the most recent events in relation to the prohibition of these practices. Description: A review and reflection analysis was performed on this practice, regarding recent questions about specific aspects of the techniques and cultural environment in which they are used. This environment is in turn influencing regulation from the technical and scientific fields, in which the health and welfare of patients should prevail. Point of view: Within medical science—a field that is in turn an art—, plastic surgery is a specialty branch of surgery and is subdivided into cosmetic and aesthetic surgery. From aesthetics, it is shown and discussed that ear cropping and tail docking do not have a scientific technical justification, unless there is a pathology or condition that requires them. Ear cropping and tail docking may have irreversible consequences on the communication and expression mechanisms of pets. Conclusions: Before performing any cosmetic surgery, animal welfare and the pros and cons of these procedures should be considered.